2021
DOI: 10.1101/2021.04.19.440419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear retention of pre-mRNA involving Cajal bodies during meiotic prophase in plants

Abstract: Gene regulation ensures that the appropriate genes are expressed at the proper times. Nuclear retention of incompletely spliced or mature mRNAs emerges as a novel, previously underappreciated layer of post-transcriptional gene regulation. Studies on this phenomenon indicated that it exerted significant impact on the regulation of gene expression by regulating export and translation delay, which allows synthesis of specific proteins in response to a stimulus, e.g. under stress conditions or at strictly controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The role of mRNAs retention in the cell nucleus in the process of post-transcriptional reduction of transcriptional noise was discovered in the last decade and is now extensively studied. It appears to be common in all eukaryotes, both unicellular, such as yeasts [11] and multicellular plants [12,13] as well as animals [14].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of mRNAs retention in the cell nucleus in the process of post-transcriptional reduction of transcriptional noise was discovered in the last decade and is now extensively studied. It appears to be common in all eukaryotes, both unicellular, such as yeasts [11] and multicellular plants [12,13] as well as animals [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested another role of nuclear mRNAs retention, namely strict temporal control of specific mRNAs export to cytoplasm [11][12][13][14]. Furthermore, regulation of gene expression by nuclear mRNA retention occurs in mammalian metabolic tissues both under stress [15,16] and normal physiological conditions [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations